CHARYFA CAKERY DALAM FOOD PHOTOGRAPHY SEBAGAI MEDIA PROMOSI INSTAGRAM - Zalfa Nadhifah; Silviana Amanda A.T; Ratih Candrastuti (Institut Seni Indonesia Yogyakarta, 2021)
Charyfa Cakery in Food Photography as Promotion Media at Instagram. Bakery is a rapidly developing culinary business. As a result, the consumption of bakery products increased, and new businesses in the culinary field began to emerge. To promote their food products, culinary entrepre- neurs use food photography. Charyfa Cakery, which produces cakes and bread with a marketing target of the upper-middle class, promotes their products through Instagram by sharing commercial photos or videos processed using photographic techniques. This research aims to create food pho- tography as a promotional tool for Charyfa Cakery to replace the previous photo on Instagram social media with available light lighting techniques and concepts that match the target market to get new consumers. The methods used in making this photo work are observation, data collection about the bakery, food photo references, interviews with the owner of Charyfa Cakery, and literature studies that can assist in the writing process. The results of this final project are food photographs with nat- ural images using available lighting techniques. Food styling and selection of property for Charyfa Cakery’s image with a middle and upper target market is a clean shot and minimalist property by utilizing the framing proportion to strengthen the impression on the main object of the photo.ABSTRAKBakery merupakan usaha yang memiliki perkembangan cukup pesat dibidang makanan. Tingginya daya tarik dan kemudahan akses dimedia digital membuat masyarakat mulai mengeksplore informasi budaya kuliner yang ada di dunia. Sehingga perkembangan konsumsi produk bakery meningkat dan mulai bermuculan usaha baru dibidang kuliner dan mempromosikan produk makanannya dalam food photography melalui media sosial Instagram dengan membagikan foto atau video yang sudah diproses dengan teknik fotografi dan dikomersilkan, antara lain Charyfa Cakery yang memproduksi kue dan roti dengan target pemasaran kalangan menengah keatas.Tujuan pembuatan karya ini adalah pemotretan food photography sebagai alat promosi Charyfa Cakery untuk menggantikan foto sebelumnya dimedia sosial Instagram dengan teknik pencahayaan available light dan konsep sesuai target market untuk mendapatkan konsumen baru.Metode yang digunakan dalam membuat karya foto ini dengan observasi data tentang bakery, referensi foto makanan, wawancara dengan pemilik Charyfa Cakery dan studi pustaka yang dapat membantu dalam proses penulisan.Hasil penelitian dari karya tugas akhir ini adalah untuk memotret makanan, teknik pencahayaan available light karena hasil gambar terkesan natural. Food styling dan pemilihan props untuk image Charyfa Cakery dengan target market menengah keatas adalah clean shot dan property yang minimal dengan memanfaatkan pembagian bidang dalam frame sehingga dapat memperkuat kesan pada objek utama foto.